EFEKTIVITAS VARIASI LAMA KONTAK ECENG GONDOK (Eichhornia crassipes) DALAM MENURUNKAN LOGAM BERAT KROMIUM HEKSAVALEN (Cr6+) PADA LIMBAH INDUSTRI PELAPISAN LOGAM - Sela Putri Herdina; Budiyono Budiyono; Suhartono Suhartono (Jurnal Kesehatan Masyarakat (Undip), 2018)
Electroplating  industry is an industry that produce hazardous waste because it contain various heavy metals such as Chromium, Copper, Nickel, Sulfate, Chloride and Cyanide compounds. The "X" electroplating industry which become the object of this research produce waste water that has 18.85 mg/L of Hexavalent Chromium and does not have a waste water treatment plant. This study aimed to determine the effectiveness of Eichhornia crassipes  to reduce hexavalent chromium level in electroplating waste water. This research used a pretest-posttest quasi-experiment research with control group. The population in this study were waste water produced by the electroplating process. The sample used in this study were 90 liters of waste water which has been diluted 50% for 9 replications and 3 controls. The statistical analysis with ANOVA test (α=5%) showed that there was a significant difference in the average reduction of Cr6+ level with different contact time. There were significant differences in the average reduction of Cr6+ levels between 5 days, 10 days and 15 days. The effectiveness level of the Cr6+ reduction showed the highest average reduction was 37.57% within 15 days contact time. The lowest Cr6+ level after treatment was 2.55 mg/L thet showed the treatment with Eichhornia crassipes had not been effective to reduce Cr6+ level to a safe limit of Cr6+ content in waste water which is 0.1 mg/L. The contact time of Eichhornia crassipes affected the reduction level of Cr6+ in electroplating waste water and the Cr6+ level decrease alongside with the increase of contact time.